Poetry Objects from the Poetry Beyond Text Project: Text, Form and Texture - Michael Roberts, Andrew (Sens public)

(untitled) (Département des littératures de langue française, 2021)
The Poetry Beyond Text project combined literary criticism, experimental psychology and practice-based research to study hybrid poetic-visual forms and practices, including artist books, engravings, poetic sculptures and digital works. Three works will be analysed here: Vivam, a wooden poetry-sculpture created by poet Deryn Rees-Jones and sculptor Marion Smith; The Wren's Egg, a poem-photograph created by Rees-Jones in collaboration with artist Alice Maher; and Poempondscroll, a poetic-photographic scroll on Chinese paper created by artist Helen Douglas and poet Valerie Gillies. Using the theories developed by Martin Seel and W.J.T. Mitchell, we will see how these collaborative works express, mediate or reconfigure the aesthetic potentials, tensions and problems surrounding the presence of poetic text in visual artworks, in order to explore the potential of the book as an object.